Separation stability in binary mixtures with negative Soret numbers - Šeta B.; Lapeira E.; Dubert D.; Gavalda F.; Bou-Ali M.M.; Ruiz X. (MATEC Web of Conferences, 2019)
In the present work, by using a paralelepipedic thermogravitational microcolumn, the temperature gradient influence on the stability of the flow was or has been examined, emphasizing mixtures with negative Soret coefficients. Experiments and numerical analysis were conducted for DCMIX2 Toulene-Methanol binary subsystem. This binary subsystem has a broad range of negative Soret values for low concentrations of Methanol which was analysed. Two different concentrations have been studied in order to confirm existence of temporal stability windows of those mixtures. Experiments were compared with numerical simulations conducted in open source software OpenFOAM, for both cases.